The Role of Helicobacter pylori Infection in Drug-induced Peptic Ulcer - Jin Sung Koh; Moon Kyung Joo (Yong Chan Lee, 2018)
Nonsteroidal anti-inflammatory drugs (NSAIDs) and low-dose aspirin (LDA) are the main causes of peptic ulcer (PU), and cause major complication such as bleeding and perforation. The interaction of Helicobacter pylori infection with NSAIDs or LDA is complex and remains unclear. However, H. pylori infection may play additive, synergistic, or antagonistic roles in the development of drug-induced PU. H. pylori infection and NSAID use are independent risk factors for the development of PU, which is thought to be a synergistic effect. Eradication of H. pylori significantly reduces the incidence of PU in NSAID-naïve patients. However, the effect of secondary prevention is controversial, especially in chronic NSAID users. The use of a gastroprotective agent such as a proton pump inhibitor (PPI) is mandatory to prevent the recurrence of PU in patients with a previous history, especially in chronic NSAID users. H. pylori infection may also increase the risk of LDA-associated complicated and uncomplicated PU, including the risk of upper gastrointestinal bleeding. In patients taking LDA, H. pylori eradication alone may prevent the recurrence of PU bleeding. However, PPI maintenance is necessary with concomitant use of an NSAID, steroid, anticoagulant, or other antiplatelet agents.